Putin, Trump and Norden: From divergence to convergence of Nordic security policies - Hans Mouritzen (Danish Institute for International Studies (DIIS), 2019)
Russia has become a more prominent Nordic security concern over the last few years. A rising threat perception and changes to the global security structure means that Nordic interests vis a vis Russia are converging. The Nordic countries interact with Russia not only in the Baltic Sea region, but also in the Barents region and in the Polar Arctic. In this working paper Swedish-Russian, Danish-Russian, Norwegian-Russian and Fenno-Russian relations are analysed diachronically within a single framework and compared. There are two sets of barriers to Nordic security and defence cooperation: (1) Nordic countries' different geopolitical interests, and (2) various idiosyncrasies between pairs of Nordic countries, typically rooted in different interpretations of their common history. Thus, the Nordic soil has traditionally been fertile for great powers seeking to "divide and rule". However, in the wake of Russia's involvement in the Ukraine conflict and the election of Donald Trump as US president, geopolitical interests seem to be converging, with fairly even perceptions of threats and opportunities being found in Nordic capitals. All four Nordic countries, in particular Sweden, face difficult dilemmas in this new situation. Security and defence cooperation will be strengthened, although a common Nordic Russia-policy is unrealistic.
Keywords: 330; small states; Russia; Nordic cooperation; divide and rule; bilateralism